Prospecção tecnológica em materiais: aumento da eficiência do tratamento bibliométrico. Aplicação na análise de tratamentos de superfície resistentes ao desgaste - Faria, Leandro Innocentini Lopes de (2001)
Nowadays, there is a wide information bulk in accelerated increase that needs high efficiency of analysis to the decision maker. Databases spreading become more important the production of indicators to technological forecasting by using automated bibliometric analysis. Although, the most databases aren t structured for this goal. In this way, it becomes fundamental the data preparation considering the technologies studied, the features of database used and of information retrieved, besides of the programming technologies. In this work, it was developed solutions to increase the efficiency of bibliometric analysis from essential databases in materials science and technology. New solution was developed to the Metadex database that allowed automatic grouping of processes, properties, factors that can influence properties and processes and shape of materials. Also, it was created a new database contained more than 30 millions of restructured records from Web of Science, inserting all the cited authors besides the first (the only one available), classification inserting, improvement of data retrieval and others. Study complementary was developed to improve the Derwent Innovation Index that improved the technological study of different countries. The methods were applied to the forecasting study of hermetic compressor surface treatments. It was possible to create and analyze indicators of the main surface treatment technologies to decrease wear, relations between applications and coatings types, among R&D fields, countries, institutions, companies and renowned researches. Also, the developed methods can be adaptable to as other databases as other technological forecasting studies like materials field or other technological and scientific knowledge fields.